Sorting of nuclear-encoded chloroplast membrane proteins - Lee, Dong Wook; Lee, Junho; Hwang, Inhwan (Current opinion in plant biology, 2017)
•Chloroplasts have three membranes, outer/inner envelopes and thylakoid membranes.•AKR2 coordinates cytosolic sorting and insertion of proteins into outer envelope.•Two pathways operate for biogenesis of inner envelope proteins.•The cpSRP pathway plays a key role in biogenesis of LHCPs into thylakoid membranes.•Besides LHCPs, most thylakoid membrane proteins are inserted spontaneously. Among the many organelles in eukaryotic cells, chloroplasts have the most complex structure, with multiple suborganellar membranes, making protein targeting to chloroplasts, particularly to various suborganellar membranes, highly challenging. Multiple mechanisms function in the biogenesis of chloroplast membrane proteins. Nuclear-encoded nascent proteins can be targeted to the outer envelope membrane directly from the cytosol after translation, but their targeting to the inner envelope and thylakoid membranes requires multiple steps, including cytosolic sorting, translocation across the envelope membranes, sorting in the stroma, and insertion into their target membranes. In this review, we discuss the current knowledge about the sorting mechanisms of proteins to the two envelope membranes and the thylakoid membrane, along with perspectives for future research.